The Effects of the Great Recession on Teenagers' Risky Health Behaviors and Time Use - Sabrina Wulff Pabilonia (Institute for the Study of Labor (IZA), 2014)
This paper uses individual-level data from both the 2003-2011 American Time Use Survey and Youth Risk Behavior Survey and state-level unemployment rates to examine the effects of the Great Recession on teenagers' activities. I present results by gender and gender by race/ethnicity. Over the period, I find changes in sexual activity for males associated with changes in time spent with parents; but results vary significantly by race. In addition, Hispanic males gained weight during the recession, due perhaps to a decrease in time spent playing sports. Hispanic females, on the other hand, made greater educational investments while spending less time working. All females significantly decreased TV viewing during the Great Recession. However, there were signs that female teenagers were stressed as they slept less and were more likely to smoke regularly.
Keywords: J22; J11; 330; teenagers; risky behaviors; time use; Great Recession; economy